Cross-cultural research methods - Ember, Carol R (Altamira Press, 2009)
The logic of cross-cultural research ;The research question; Theories and hypotheses; The art of measurement ; Minimizing error -- Sampling -- Coding data -- The basics of statistical analysis -- Reliability -- Introducing multivariate analysis; Summing up.